2007
DOI: 10.1111/j.1463-1326.2007.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the dipeptidyl peptidase‐4 inhibitor, sitagliptin, in patients with type 2 diabetes mellitus inadequately controlled on glimepiride alone or on glimepiride and metformin

Abstract: Aim: To assess the efficacy and safety of a 24-week treatment with sitagliptin, a highly selective once-daily oral dipeptidyl peptidase-4 (DPP-4) inhibitor, in patients with type 2 diabetes who had inadequate glycaemic control [glycosylated haemoglobin (HbA 1c ) !7.5% and 10.5%] while on glimepiride alone or in combination with metformin. Methods: After a screening, diet/exercise run-in and drug wash-off period, a glimepiride AE metformin dose titration/ stabilization period and a 2-week, single-blind placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
390
11
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(447 citation statements)
references
References 22 publications
(30 reference statements)
41
390
11
5
Order By: Relevance
“…Previous studies showed that DPP‐4 inhibitor was effective as an add‐on therapy to some antidiabetic drugs, including metformin 22 , pioglitazone 23 and sulfonylurea 24 . The profile of diabetic therapy before DPP‐4 inhibitor administration was as follows: 16 used diet, 15 received sulfonylurea monotherapy, 12 received metformin monotherapy, eight received sulfonylurea and metformin, five received sulfonylurea and pioglitazone, two received sulfonylurea and alpha‐glucosidase inhibitor, and four took three drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that DPP‐4 inhibitor was effective as an add‐on therapy to some antidiabetic drugs, including metformin 22 , pioglitazone 23 and sulfonylurea 24 . The profile of diabetic therapy before DPP‐4 inhibitor administration was as follows: 16 used diet, 15 received sulfonylurea monotherapy, 12 received metformin monotherapy, eight received sulfonylurea and metformin, five received sulfonylurea and pioglitazone, two received sulfonylurea and alpha‐glucosidase inhibitor, and four took three drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This may be of interest in patients who cannot be treated with metformin. Compared with a placebo, sitagliptin 100 mg (once daily) [45] and vildagliptin (50 or 100 mg daily) [46] significantly improved glycaemic control and β-cell function, and were well tolerated in T2DM patients with inadequate glycaemic control with glimepiride alone. Similar results were reported in T2DM patients with the addition of alogliptin (12.5 mg or 25 mg) to glyburide [47] and the addition of linagliptin (5mg) to a SU [48].…”
Section: Gliptins Combined With Sulphonylureasmentioning
confidence: 99%
“…Again, most studies, except one [63], were randomized clinical trials comparing the addition of a gliptin vs a placebo on top of a dual combination of either metformin-SU [45,64] or metformin-TZD [65]. Sitagliptin 100mg once daily significantly improved glycaemic control and β-cell function in patients with T2DM who had inadequate glycaemic control with glimepiride plus metformin therapy [45]. Similarly, adding linagliptin 5 mg to metformin in combination with SU significantly improved glycaemic control in T2DM patients and was well tolerated [64].…”
Section: Gliptins As Oral Triple Therapymentioning
confidence: 99%
“…It was found to be in tune with other studies of sitagliptin combined with metformin done by Charbonnel et al and Hermansen et al who observed a reduction of 0.7% and 0.74% respectively. 8,9 Both these studies were of 24 weeks duration.…”
Section: Discussionmentioning
confidence: 99%